2011
DOI: 10.1089/dia.2011.0121
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Physical Activity on Metabolic State Within a 3-h Interruption of Continuous Subcutaneous Insulin Infusion in Patients with Type 1 Diabetes

Abstract: The influence of physical activity during a 3-h interruption of insulin pump treatment is evident, especially in the increase in plasma levels of non-esterified fatty acids and ketone bodies. Correction bolus leads to a rapid increase in insulinemia; however, normalization of blood glucose and ketone bodies is achieved within another 90 min.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(20 citation statements)
references
References 23 publications
0
20
0
Order By: Relevance
“…During the process of peer review for this report, journal reviewers identified one extra study that fulfilled our inclusion criteria: Yardley et al [28]. Table 1 summarizes the main characteristics of the final ten publications [28][29][30][31][32][33][34][35][36][37] incorporated in this systematic review and meta-analysis.…”
Section: Study Characteristicsmentioning
confidence: 99%
See 4 more Smart Citations
“…During the process of peer review for this report, journal reviewers identified one extra study that fulfilled our inclusion criteria: Yardley et al [28]. Table 1 summarizes the main characteristics of the final ten publications [28][29][30][31][32][33][34][35][36][37] incorporated in this systematic review and meta-analysis.…”
Section: Study Characteristicsmentioning
confidence: 99%
“…Three publications did not clearly comment on preceding physical activity [28,29,35]. In addition, three protocols [30,32,33] checked for the absence of hypoglycemia during the hours or days prior to the exercise sessions and postponed the study in the case of recent hypoglycemic events.…”
Section: Risk Of Biasmentioning
confidence: 99%
See 3 more Smart Citations